2020
DOI: 10.1177/0960327120954249
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 prevents AOM/DSS-induced colitis-associated colorectal cancer in Bacteroides fragilis gnotobiotic mice

Abstract: Bacteroides fragilis (BF) plays a critical role in developing and maintaining the mammalian immune system. We previously found that BF colonization could prevent inflammation and tumor formation in a germ-free (GF) colitis-associated colorectal cancer (CAC) mouse model. The role of Toll-like receptor 4 (TLR4) in CAC development has not been clearly elucidated in BF mono-colonized gnotobiotic mice. The wild-type (WT) and TLR4 knockout (T4K) germ-free mice were raised with or without BF colonization for 28 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This may be related to the protective effect of it by inhibiting TNF-α-induced apoptosis and injury. NF-κB is a ubiquitously expressed transcription factor that acts as a critical regulator of immune and in ammatory response and programmed cell death [44]. Our results showed that the NF-κB signaling pathway was slightly activated and it was not statistically signi cant when treatment with B. fragilis alone.…”
Section: Discussionmentioning
confidence: 64%
“…This may be related to the protective effect of it by inhibiting TNF-α-induced apoptosis and injury. NF-κB is a ubiquitously expressed transcription factor that acts as a critical regulator of immune and in ammatory response and programmed cell death [44]. Our results showed that the NF-κB signaling pathway was slightly activated and it was not statistically signi cant when treatment with B. fragilis alone.…”
Section: Discussionmentioning
confidence: 64%
“…The positivity rates of ETBF were 67.3%, 72.7% and 100% for colonoscopic biopsy samples from healthy, early, and advanced CRC patients [ 16 ], suggesting a trend of ETBF enrichment with CRC progression. ETBF has also been demonstrated to accelerate CRC development and progression by regulating inflammatory responses [ 17 ], dryness [ 18 ], and polyp formation [ 19 , 20 ]. BFT secretion is one of the main pathways through which ETBF facilitates the CRC development process [ 19 , 21–23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the protective effect of it by inhibiting TNF-α-induced cell injury. NF-κB is a ubiquitously expressed transcription factor that acts as a critical regulator of immune and inflammatory response and programmed cell death 33 . Our results showed that the NF-κB signaling pathway was slightly activated and it was not statistically significant when treatment with B. fragilis ATCC25285 alone.…”
Section: Discussionmentioning
confidence: 99%